Antimutagenic and Chemopreventive Properties of 6-(Methylsulfinyl) Hexyl Isothiocyanate on TK6 Human Cells by Flow Cytometry - Cocchi, Veronica; Hrelia, Patrizia; Lenzi, Monia (Frontiers in Pharmacology, 2020)
6-(methylsulfinyl) hexyl isothiocyanate (6-MITC), is the main bioactive compound present in Wasabia Japonica rhizome. Several scientific studies have shown that 6-MITC possesses interesting antimicrobial, anti-inflammatory, antiplatelet and antioxidant properties which therefore suggested us it could have an interesting chemopreventive potential. In a recent publication, we demonstrated, in two different leukaemia cell lines, its ability to modulate several mechanisms supporting its antitumor activity. For this reason, we thought useful to continue the research, by investigating the potential antimutagenic activity of 6-MITC and thus better define its profile as a possible chemopreventive agent. 6-MITC antimutagenic effect against two known mutagenic agents: the clastogen Mitomycin C (MMC) and the aneuplodogen Vinblastine (VINB), was analyzed, in terms of micronuclei frequency decrease, after short- and long- time treatment on TK6 human cells, using a new automated protocol of the “In Vitro Mammalian Cell Micronucleous Test” by flow cytometry. The results showed a different behavior of the isothiocyante. In particular, 6-MITC was unable to counteract the MMC genotoxicity, but when it was associateed with VINB a statistically significant decrease in the micronuclei frequency was registered. Overall, the results obtained suggest a potential antimutagenic activity of 6-MITC, in particular against the aneuploidogen agents. This ability, to inhibit or counteract the mutations at the cellular level has a great therapeutic value and it represents a mechanism through a chemopreventive agent can express its activity.